Keunggulan dan Potensi Pengembangan Sumber Daya Genetik Durian Kalimantan Tengah - Amik Krismawati (Buletin Plasma Nutfah, 2012)
Superiority and Potential Development of Durio Germplasm in Central Kalimantan. Amik Krismawati. Indonesia is rich of genetic resources and biodiversity of Durio spp., but its development no so fastly as in Thailand. This is due to plant durio has not managed commercially and it grew hundred years and it origin from generative propagation, caused the durio plantation variety heterogen. To determine the performance and advantage of the diversity of genetic resources should be conducted observations of durio related species the characterization in each district centre. Observation and characterization of related species of durio e.i. Durio zibethinus M. (durian), Durio kutejensis H.B (papaken), Durio oxleyanus (kerantungan/taetungen), and Durio dulcis (layung) were conducted in four districts of Central Kalimantan from August 2004 to January 2005. Seasons fruity and yield of each species to variously among the durio and its related species. Differences among accesions were characterized by fruit type, fruit shape, fruit skin texture, fruit length, fruit skin colour, fruit flesh colour, and taste. The fruiting season and fruit production of each species also varied durio relatives.The result of characterization showed the related species of Durio are indigenous of Indonesia and potencially to development in the future. AbstrakIndonesia kaya akan sumber plasma nutfah dan keragaman jenis durian (Durio spp.), namun pengembangannya tidak sepesat Thailand. Hal ini disebabkan tanaman durian belum dikelola secara komersial dan tanaman yang ada umumnya sudah berumur ratusan tahun yang berasal dari perbanyakan generatif sehingga tidak memberikan hasil yang optimal. Untuk mengetahui keunggulan dari keanekaragaman sumber daya genetik durian maka dilakukan observasi dan karakterisasi di beberapa lokasi di empat kabupaten di Kalimantan Tengah dari Agustus 2004 hingga Januari 2005. Kerabat durian yang diobservasi dan dikarakterisasi adalah durian (Durio zibethinus M.), papaken (Durio kutejensis H.B.), kerantungan/taetungen (Durio oxleyanus), dan layung (Durio dulcis). Hasil karakterisasi menunjukkan bahwa karakter buah antarspesies kerabat durian sangat bervariasi. Perbedaan di antara spesies tersebut terletak pada tipe buah, bentuk buah, tekstur kulit buah, panjang buah, warna kulit buah, warna dan rasa daging buah. Musim berbuah dan produksi masing-masing spesies kerabat durian juga bervariasi. Kerabat durian dari jenis Durio (Durio spp.) yang merupakan tanaman asli Indonesia berpotensi dikembangkan.